Linking ESG and EMA to Firm Value The Moderating Role of Green Innovation - Adelia Rifa Sabila; Lenni Yovita; Vicky Oktavia; Suhita Whini Setyahuni (International Journal of Economics, Management and Accounting, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) and Environmental Management Accounting (EMA) on firm value, with Green Innovation (GI) as a moderating variable. The research is based on secondary data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, analyzed using path analysis with a moderated regression approach in SPSS. The findings reveal that ESG has a significant but negative impact on firm value, suggesting that ESG investments may be perceived as cost burdens in the short term. Meanwhile, EMA does not have a significant effect on firm value, indicating that its role in firm valuation remains unclear. The moderating role of GI does not significantly strengthen the relationship between ESG and firm value, while the interaction between EMA and GI negatively affects firm value,implying that green innovation strategies may introduce additional financial burdens. These findings highlight the complexity of sustainability investments and emphasize the need for a balanced approach to ESG and EMA implementation to optimize long-term firm value. The study contributes to legitimacy and stakeholder theories by demonstrating how sustainability strategies can influence financial outcomes. It provides practical insights for businesses to develop more effective ESG disclosure and EMA implementation strategies that align with investor expectations and long-term firm sustainability